Transaksi gharar dalam islam: analisis berdasarkan al-quran dan hadits - Gunawan, Gunawan (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the concept of gharar in Islamic law and analyze its application in modern economic transactions. Gharar is one of the important prohibitions in muamalah fiqh because it contains an element of uncertainty that can harm one of the parties in the transaction. In contemporary economic practice, gharar can be found in various forms such as online buying and selling, derivative instruments, and transactions that are not accompanied by clarity of the object, price, or time of delivery. This study uses a qualitative method with a literature study approach. Data were obtained from primary and secondary literature in the form of the Qur'an, hadith, fiqh books, scientific journals, and fatwas from the National Sharia Council (DSN-MUI). The results show that forms of gharar in the modern economy have a negative impact on justice and legal certainty in transactions. Therefore, an understanding of sharia principles is needed, as well as strengthening regulations and education to realize an ethical and sustainable transaction system in accordance with Islamic values.